Expression of a specific variant surface glycoprotein has a major impact on suramin sensitivity and endocytosis in Trypanosoma brucei. Issue 10 (30th September 2019) - Wiedemar, Natalie; Zwyer, Michaela; Zoltner, Martin; Cal, Monica; Field, Mark C.; Mäser, Pascal
Abstract: Suramin was introduced into the clinic a century ago and is still used to treat the first stage of acute human sleeping sickness. Due to its size and sixfold negative charge, uptake is mediated through endocytosis and the suramin receptor in trypanosomes is thought to be the invariant surface glycoprotein 75 (ISG75). Nevertheless, we recently identified a variant surface glycoprotein (VSG Sur ) that confers strong in vitro resistance to suramin in a Trypanosoma brucei rhodesiense line. In this study, we introduced VSG Sur into the active bloodstream expression site of a T. b. brucei line. This caused suramin resistance and cross resistance to trypan blue. We quantified the endocytosis of different substrates by flow cytometry and showed that the expression of VSG Sur strongly impairs the uptake of low‐density lipoprotein (LDL) and transferrin, both imported by receptor‐mediated endocytosis. However, bulk endocytosis and endocytosis of the trypanolytic factor were not affected, and the VSG Sur ‐expressors did not exhibit a growth phenotype in the absence of suramin. Knockdown of ISG75 was synergistic with VSG Sur expression, indicating that these two proteins are mediating distinct suramin resistance pathways. In conclusion, VSG Sur causes suramin resistance in T. brucei bloodstream forms by decreasing specific, receptor‐mediated endocytosis pathways.